Navigation Control of a Multi-Functional Eye Robot: Navigation Control of a Multi-Functional Eye Robot - Ahmed, Farhan; Ali, Muhammad; Hashmi, Bilawal; Younas, Adeel; Abid, Bilal (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The advancement in robotic field is enhanced rigorously in the past few decades. Robots are being used in different fields of science as well as warfare. The research shows that in the near future, robots would be able to serve in fighting wars. Different countries and their armies have already deployed several military robots. However, there exist some drawbacks of robots like their inefficiency and inability to work under abnormal conditions. Ascent of artificial intelligence may resolve this issue in the coming future. The main focus of this paper is to provide a low cost and long range most efficient mechanical as well as software design of an Eye Robot. Using a blend of robotics and image processing with an addition of artificial intelligence path navigation techniques, this project is designed and implemented by controlling the robot (including robotic arm and camera) through a 2.4 GHz RF module manually. Autonomous function of the robot includes navigation based on the path assigned to the robot. The path is drawn on a VB based application and then transferred to the robot wirelessly or through serial port. A Wi-Fi based Optical Character Recognition (OCR) implemented video streamingcan also be observed at remote devices like laptops.